Single microwave-photon detector using an artificial Λ-type three-level system - Kunihiro Inomata (Nature Portfolio, 2016)
Single-photon detection is challenging in the microwave regime due to the small photon energy. Here, the authors demonstrate the deterministic detection of single microwave photons through an impedenance-matched artificial Λ system composed by a driven superconducting qubit and a microwave resonator.